BLOG DA SAÚDE COMO FERRAMENTA PARA A UTILIZAÇÃO DA SISTEMATIZAÇÃO DA ASSISTÊNCIA DE ENFERMAGEM - Rocha, Luciana Denize Molino da (2019)
Introduction: The Systematization of Nursing Care is a tool that assists in the process of care performed by the nurse, in the consultations in which the care performed is ordered with greater efficiency and responsibility. The Systematization of Nursing Care requires nurses to know the patient as an individual, using their knowledge and skills, as well as guidance and training of the nursing team for the implementation of systematized actions. The use of technology in health can be seen by the numerous tools available in the market, through specific applications. The use of tools, such as blogs, can favor the improvement of diagnoses, enabling treatments with greater efficiency and quality, which may impact on the management of the operational costs of the clinical services rendered. In view of this context, the present study has as a guiding question: how can the construction of a health blog favor the implementation of Nursing Care Systematization in usual risk prenatal care. General objective: To construct a health blog with information about the use of the Systematization of Nursing Assistance in the consultation of prenatal usual risk. Specific objectives: Identify the Brazilian publications about the application of SAE in the consultations to pregnant women in Primary Care. To investigate how the nursing consultation in prenatal care of usual risk in Basic Care is being performed in a medium-sized municipality of Rio Grande do Sul? What are the weaknesses and needs related to SAE referred by nurses who attend prenatal women in Primary Care. Method: This is a qualitative, exploratory descriptive study, carried out from October to December, 2018. Participants were 15 nurses who work in Family Health Strategy in the central region of Rio Grande do Sul. Results: Manuscript 1 - Systematization of Nursing Assistance to pregnant women in Primary Care: an integrative review. Product generated: Health Blog - Systematization of Nursing Assistance in low risk prenatal consultation; Manuscript 2 - Reflections on the Systematization of Nursing Care in prenatal care at usual risk. As a result of this research we have the Blog of Health, which brings the main nursing diagnoses to pregnant women at usual risk attending primary care.